Hokusai 1760-1849 - Paget, Rhiannon (Köln, Germany Taschen, 2018)
"Meet the artist whose majestic breaking wave sent ripples across the world. Hokusai (1760-1849) is not only one of the giants of Japanese art and a legend of the Edo period, but also a founding father of Western modernism, whose prolific gamut of prints, illustrations, paintings and other works forms one of the most comprehensive oeuvres of ukiyo-e art and a benchmark of Japonisme. His influence spread through Impressionism, Art Nouveau and beyond, enrapturing the likes of Claude Monet, Berthe Morisot, Paul Gauguin and Vincent van Gogh."
Capturing the Floating World--
The Fellow Mad about Painting--
Born Again--
Divine Madness--
Hokusai 1760-1849, Life and Work--
Includes bibliographical references
Keywords: Katsushika, Hokusai -- 1760-1849 -- Criticism and interpretation; Color prints, Japanese; Ukiyoe; Wood-engraving, Japanese